Recording vegetation composition at the Siberian boreal treeline: A comparison between sedimentary DNA and pollen. - Niemeyer, Bastian; Epp, Laura Saskia; Stoof-Leichsenring, Kathleen Rosmarie; Pestryakova, Ludmila A; Herzschuh, Ulrike (PANGAEA, 2016)
Reliable information of past vegetation changes are important to project future changes, especially for areas undergoing rapid transitioning such as the boreal treeline. The application of detailed sedDNA records has the potential to enhance our understanding of vegetation changes gained mainly from pollen studies of lake sediments. This study investigates sedDNA and pollen records from 31 lakes along a gradient of increasing larch forest cover in northern Siberia (Taymyr Peninsula) and compares them with vegetation field surveys within the lake's catchment. With respect to vegetation richness, sedDNA recorded 114 taxa, about half of them to species level, while pollen analyses identified 43 pollen taxa. Both approaches exceed the 31 taxa revealed by vegetation field surveys of 400 m**2 plots. From north to south, Larix percentages increase, as is consistently recorded by all three methods. Furthermore, tundra sites are separated from forested sites in the plots of the principal component analyses. Comparison of ordination results by Procrustes and Protest analyses yields a significant fit among all compared pairs of records. Despite the overall comparability of sedDNA and pollen analyses certain idiosyncrasies in the compositional signal are observed, such as high percentages of Alnus and Betula in all pollen spectra and high percentages of Salix in all sedDNA spectra. In conclusion, our results from the treeline show that sedDNA analyses perform better than pollen in recording site-specific richness (i.e. presence/absence of certain vegetation taxa in the direct vicinity of the lake) and perform as good as pollen in tracing regional vegetation composition.
Pollen, DNA and Vegetation records from surface sediments of lacustrine lakes along a forest tundra - tundra transect at the Taymyr peninsula, northern Siberia
Keywords: AWI_PerDyn; Permafrost Research (Periglacial Dynamics) @ AWI